The Factors Influencing Residential Satisfaction by Public Rental Housing Type. Issue 3 (1st September 2016) - Byun, Gidong; Ha, Mikyoung
Abstract : The purpose of this study is to determine the level of satisfaction among residents in public rental housing to solve the housing problems of low-income households. From among the various types of public rental housing, those with large differences in the physical housing environment were selected for an analysis of the environmental factors impacting tenants′ residential satisfaction. To achieve the study′s objective, the residential satisfaction of tenants in public residential housing in Seoul was researched and analyzed; results are as follows. First, the environmental factors impacting individuals living in public rental housing were described as the ″Safety and Incivility Factor″ (SIF), ″Physical Factor″ (PF), ″Facilities Accessibility Factor″ (FAF), and ″Equipment Factor″ (EF). Second, these factors were found to impact residential satisfaction of tenants in public rental apartments in the order of EF, SIF, PF, and FAF; they were found to impact the tenants of public rental general houses in the order of SIF, EF, PF, and FAF. These differences are based on the public rental housing type, which necessitates plans that consider priority improvement of residential environment factors according to housing types, to improve the residential satisfaction of tenants in both currently operating and future public rental housing.